1346. The Risk of Readmission after RSV Hospitalization Among Children Younger than 5 Years. (4th December 2021) - Choi, Yoonyoung; Heller, Evan G; Gesteland, Per H; Amoafo, Linda; Zhang, Yue; Finelli, Lyn; Ampofo, Krow
Abstract: Background: Respiratory Syncytial Virus (RSV) is one of the most common causes of childhood lower respiratory tract infection (LRTI) leading to hospitalization worldwide. Readmissions following viral LRTI hospitalization are common, however rates, timing and causes of readmission following RSV LRTI hospitalization are understudied. We evaluated readmissions occurring during 1-year post-discharge of RSV hospitalization. Methods: We prospectively identified children < 5 years of age hospitalized with laboratory-confirmed RSV LRTI at Primary Children's and Riverton hospitals in Salt Lake City, Utah during the 2019-2020 RSV season. An electronic alert system identified all-cause readmission between November 2019 and April 2021. Discharge diagnoses of readmissions were reviewed by two pediatricians. We calculated the incidence rate of all-cause and respiratory-related readmission. Results: A total of 297 children had laboratory-confirmed RSV LRTI hospitalizations during the 2019-2020 RSV season, with 24% admitted to the intensive care unit (ICU) during index RSV hospitalization and 24% having a chronic medical condition. During the 1-year follow-up period, 59 readmissions occurred among 47 patients (Table 1). The incidence rate of all-cause and respiratory-related readmission was 19.9 (95%CI 15.5-24.9) and 13.1 (95%CI 9.5-17.5) per 100 patients, respectively. Median age of readmitted patients was 11 months (interquartile range 5.9-11 months). Median number of readmissions was 1 (range: 1-4), with initial readmissions occurring within 28 days (median) of index admission; most (74%) due to a respiratory-related illness. Second and 3 rd admissions were less common and occurred at 67 (median) and 160 (median) days respectively. During all readmissions, 19% of children required ICU admission and 25% had chronic medical conditions. Conclusion: All cause and respiratory readmission after Initial hospitalization with RSV LRTI commonly occurred among children < 5 years. These data support the need for RSV vaccines and immunoprophylaxis to prevent RSV hospitalization. A further study with a control group is needed to determine the role of RSV in readmission. Disclosures: Yoonyoung Choi, PhD, MS, RPh, Merck (Employee) Lyn Finelli, DrPH, MS, Merck (Employee)